Nerve block in hernioplasties with Shouldice technique - Ferrari, Luis Carlos; Comin, Raúl Alberto; Manna, Ruben; Pesenti, Dante; La Valva, Víctor Salvador; Molina Rivero, Luis (Cirugía del Uruguay, 1995)
Fifteen inguinal hernioplasties performed with local anesthesia by nerve blockade and Shoudice's technique are presented in the general surgery department nº 3 of San Roque Hospital, Córdoba, Argentina. lt is attempted in this present work to help on spreading both procedures having in mind the accuracy, the effect reversibility and the technica/ good acceptance by nerve blockade even in patients with high anesthesic risk, added to a diligent, modern and thorough technique of hernia/ repair which we have previously carried out with an excellent result.